Challenges and Opportunities to Climate Change Adaptation and Sustainable Development Among Tanzanian Rural Communities (Sustainability in Debate, 2010)
In more recent years climate change impacts have been obvious around the globe. This non-contentious reality has resulted in various global initiatives to reduce climate change impacts. However, differences exist in opportunities and capacity to adaptation. This paper, descriptive in nature, draws heavily from literature and also uses 2002 Tanzanian population and housing census to identify and discuss major challenges and opportunities to climate change adaptation and sustainable development in rural areas of Tanzania. Two groups are of focus; pastoralist herders and smallholder farmers. Analysis indicates that opportunities to climate change adaptation among rural community include their knowledge and experience. Challenges are centered on the pervasive poverty, rapid population increase and high illiteracy rates. Forces beyond their control including funds and governance also present definite limits to climate change adaptation. The paper suggests among others, the effective implementation of two top policies: education and social security funding.